New Brilliant Blue G Derivative as Pharmacological Tool in Retinal Surgery - Spadaro, Angelo; Rao, Marco; Lorenti, Miriam; Romano, Mario Rosario; Augello, Antonio; Eandi, Chiara Maria; Platania, Chiara Bianca Maria; Drago, Filippo; Bucolo, Claudio (Frontiers in Pharmacology, 2020)
Our study was aimed to asses the retinal binding of a new synthetic Brilliant Blue G derivative (PBB) ophthalmic formulation to improve vitreoretinal surgery procedure. Protein affinity of the new molecule was evaluated in vitro (cell-free assay) and in silico. Further, an ex vivo model of vitreoretinal surgery was developed by using porcine eyes to assess the pharmacological profile of PBB compared to commercial formulations based on Brilliant Blue G (BBG) and methyl-BBG (Me-BBG). PBB showed a higher affinity for proteins (p<0.05) compared to BBG and Me-BBG. In vitro and in silico studies demonstrated that the high selectivity of PBB could be related to the high lipophilicity and binding to fibronectin, the main component of the retinal internal limiting membrane (ILM). Furthermore, PBB staining capabilities were evaluated in porcine eyes in comparison with BBG and Me-BBG. Forty microliters of each formulation were slowly placed over the retinal surface and removed after 30 seconds. After that ILM peeling was carried out, and the retina collected. BBG, Me-BBG and PBB quantification in ILM and retina tissues was carried out by HPLC analysis. PBB levels in the ILM were significantly (p<0.05) higher compared to BBG and Me-BBG formulations. On the contrary, PBB showed a significant lower (p<0.05) distribution in retina (52 ng/mg tissue) compared to BBG and Me-BBG, in particular PBB levels were significantly (p<0.05) lower. Therefore, the new synthetic Brilliant Blue derivative (PBB) showed a great ILM selectivity in comparison with underneath retinal layers. In conclusion, these findings had high translational impact with a tangible improving of retinal surgery, suggesting a future use during surgical practice.